Selected physiological responses of Salvinia minima to different chromium concentrations - Nichols, P.B.; Couch, J.D.; Al-Hamdani, S.H.
This laboratory study was designed to evaluate the influence of Cr(VI)concentrations of 1 and 2mg l-1 on selected physiological responses of Salvinia minima (Willd). In addition, the uptake of Cr by salvinia was measured. Salvinia growth, and CO2 uptake was significantly reduced in the presence of chromium. The same result was obtained for chlorophyll a, chlorophyll b, and carotenoid concentrations. Most of the negative Cr(VI)influence was shown during the second week of the experiment. Plant light harvesting capacity, specifically for blue and red wavelengths was reduced with increases in Cr(VI)concentrations. In addition, soluble sugar, starch, and total nonstructural carbohydrate concentrations significantly increased as did chromium Cr(VI)accumulation.
Keywords: SALVINIA MINIMA; CHROMIUM; CHLOROPHYLL; CAROTENOID; CARBOHYDRATE; GROWTH